The folk culture of the boi-bumbá at school: propositions for thinking about an interdisciplinary pedagogical action (Research, Society and Development, 2021)
This article aims to describe the folk culture of Boi-Bumbá at the Federal Institute of Science and Technology of Rondônia – IFRO/Campus Cacoal and its approaches to the school pedagogical practice for the interdisciplinary teaching of Art. The collaborating subjects were professors and students of this institution. The methodology was based on the qualitative approach to bricolage (Kincheloe, J.L. & Berry, K.S. 2007) and used several research techniques supported by the Post-Critical perspective and by Cultural Studies. The research with the professors showed their relationship with folklore in their monodisciplinary work and their desire to turn to the field of interdisciplinarity. The work with students provided data on popular culture and daily life. This information helped in the construction of an Interdisciplinary Didactic Sequence with the theme Boi-Bumbá and contents of the curricular components of Geography, History, Sociology, Physical Education, Modern Foreign Language/Spanish, Portuguese Language/Brazilian Literature and Art, and makes us conclude that it is possible integrate the knowledge of the community with the official contents and build, interdisciplinary, an intercultural education in favor of a democratic and inclusive society.